(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The effect of head groups on the thermodynamic properties and morphological features of the domains formed in the Langmuir monolayers at 10 oC has been investigated by a film balance and a Brewster angle microscopy (BAM). 2-hydroxyethyl myristate (2-HEM) and n-tetradecanoyl N-ethanolamide (NHEA-14), having the same chain length but different head groups have been taken as amphiphiles. Both the amphiphiles represent a first-order LE-LC phase transition at 10 oC at the air-water interface. The critical surface pressure necessary for this phase transition is 6.0 mN/m for 2-HEM and 1.0 mN/m for NHEA-14. The surface morphologies of the domains are entirely different. The domains of 2-HEM are circular having internal texture, while those of NHEA-14 are dendritic having directional characteristics. The presence of interfacial hydrogen bonding in the latter amphiphile should be responsible for the formation of such characteristic domains in the case of latter amphiphile. Key words: Langmuir monolayers; Phase transition; Brewster angle microscopy; 2-hydroxyethyl myristate; n-tetradecanoyl Nethanolamide. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8104 Bangladesh J. Sci. Ind. Res. 46(1), 47-52, 2011